Home-Making among South Andean Pastoralist: La constitución del hogar entre los pastores del centro-sur andino - Nielsen, Axel E. (2024)
I analyze the practices related to home-making among llama pastoralists in the South-Central Andes, a process which is understood as a continuous negotiation among different kinds of persons, both human and nonhuman. I start by conceptualizing pastoralism as a social interaction network involving herders, their animals, the community (as the owner of the land), and various deities. Then, I analyze how llameros negotiate the placement of the house with each one of these agents, according to a logic that is explicitly manifested in ritual. In order to illustrate this point, I describe the k’illpa or «flowering» of the animals, the main domestic ritual of the annual cycle. I put emphasis on the ritual gestures and the way in which they express and reproduce this social fabric which defines the place of each family in the territory and in the world.